Ученые-репатрианты из бывшего СССР: социально-языковая самоидентификация и профессиональная интеграция в Израиле - Эпштейн, А.; Хеймец, Н.; Патлас, Н. (Социология: теория, методы, маркетинг, 2000)
The purpose of this study is to analyze various sociological and psychological factors that influence the immigrant scientists’ integration into the Israeli society in general, and its academic community in particular. To examine the above mentioned aspects, the questionnaire containing 135 multiple-choice questions has been composed. The number of respondents amounted to 130, which constituted 1% of the number of scientists from the former Soviet Union who live in Israel. Special attention is paid to the analysis of the immigrant scientists’ multilingual identity. This study examines the effect of the foreign language studied within the formal education framework on one’s adjustment to the host society as well as on his/her estimation of the chances to succeed in the new circumstances. The previous studies conducted in this field juxtaposed Russian with Hebrew, assigning English with merely an instrumental function and thus ignoring its importance for the immigrants’ self-image. In this study English is considered a crucial factor which does not only influence the process of one’s adaptation to the new society, but also takes part in shaping the patterns of one’s integration into it.